Indirect electrochemical detection of perfluoro decanoic acid from water - Sorina-Claudia Negrea; Lidia Ani Diaconu; Dorian Neidoni; Adina Pacala; Luoana Florentina Pascu; Sorina Motoc; Anamaria Baciu; Elena Trif; Florica Manea (Romanian Journal of Ecology & Environmental Chemistry)
Electrochemical detection of perfluoro decanoic acid (PFDA) has gained significant interest due to the its environmental persistence and potential health risks. This study focuses on the development and utilization of a molecular imprinted polymer (MIP) sensor for the selective and sensitive detection of PFDA in aqueous samples. Commercial boron-doped diamond (BDD) electrode was modified with MIP by electro polymerization in 2:1 (v/v) mixture of 0.1 M sodium acetate buffer solution (pH = 5.8) and methanol containing 10 mM o-phenylenediamine (o-PD) and 1 mM PFDA concentration. The electro polymerization process was carried out using cyclic voltammetry (CV) by scanning 25 cyclic voltammograms in a potential range of 0.00 →1.00 V/SCE with a scan rate of 0.05 V·s-1. The electrochemical performance of the MIP-BDD sensor using cyclic voltammetry (CV), differential pulse voltammetry (DPV) and square wave voltammetry (SWV) was assessed. Considering both voltametric detections based on oxygen reduction reaction (ORR) and the lack of electrochemical activity of PFDA, investigation of its signal in the presence of increased PFDA concentrations is exploited for development of indirect detection method. Linear dependence between signal decrease vs. increasing PFDA concentrations allowed determining sensitivity and the lowest limit of detection of 0.160 nM (0.08 µg·dm-3) PFDA. The integration of MIP technology with electrochemical sensors offers a robust platform for environmental monitoring of PFDA, combining high selectivity, sensitivity and rapid response time. This method holds promise for advancing detection techniques for persistent organic pollutants in environmental and public health contexts.